The training and detraining effects of 8-week dynamic stretching of hip flexors on hip range of motion, pain, and physical performance in male professional football players with low back pain. A randomized controlled trial - Iranmanesh, M.; Nikou, S. S.; Saadatian, A.; Alimoradi, M.; Khalaji, H.; Monfaredian, O.; Saki, F.; Konrad, A. (Journal of Sports Sciences, 2025)
This randomized controlled trial examined the efficacy of an 8-week dynamic stretching (DS) intervention in 40 professional male football players (mean age 24.3 ± 4.5 years; height 177.3 ± 5.3 cm; body mass 72.7 ± 5.1 kg) presenting with chronic low back pain (LBP) and hip flexion limitations. Participants were equally randomized to either an experimental group (n = 20) performing supervised DS exercises five times weekly or a control group (n = 20) maintaining regular training. Comprehensive assessments conducted at baseline, 4, 8, and 12 weeks demonstrated that the intervention group achieved statistically significant improvements in: hip range of motion (ROM) (dominant leg: 3.01 effect size [ES], p = 0.001; non-dominant leg: 3.06 ES, p = 0.001), pain reduction (ES = 0.85, p = 0.001), dynamic balance (dominant leg: 0.30 ES, p = 0.001), and countermovement jump performance (ES = 0.31, p = 0.001). No significant enhancements were observed in 20-meter sprint times or agility test performance (p > 0.05). The subsequent 4-week detraining period resulted in partial but significant loss of gains across multiple outcomes including hip ROM (dominant: 0.80 ES; non-dominant: 0.64 ES, both p = 0.001) and pain relief (ES = 0.40, p = 0.001), indicating that sustained clinical benefits require ongoing implementation of the stretching protocol. These findings support the utility of DS for managing LBP in football athletes while highlighting the importance of program continuity.